Palisaded Encapsulated Neuroma (PEN): A Case Report - Samdurkar, A; Poudel, S; Regmi, S; Khurana, S (Journal of Universal College of Medical Sciences, 2013)
A growth or tumor of nerve is neuroma. Localised and circumscribed neuromas are termed as true neoplasm, as per James W. Patterson's quotation. Further, Palisaded encapsulated Neuroma (PEN) is a distinctive cutaneous nodular lesion often in the head, neck and face regions and are benign. They have schwannian and axonal components. A 30 year old male presented to surgical OPD with nodular enlargement in the scar behind the ear. Grossly these are usually pear shaped or bulb like dermal nodule. Microscopy showed peripheral circumscription for nodules of axonal and schwannian cells with predominance of fibroblastic component. Various references support above findings. And therefore, we arrived to a conclusion of this being PEN within scar tissue, as regards to clinical and histopathlogic peculiarities both gross and microscopic. DOI: http://dx.doi.org/10.3126/jucms.v1i1.8420 Journal of Universal College of Medical Sciences Vol.1(1) 2013: 28-32